2019
DOI: 10.21037/jgo.2019.02.14
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-122 in patients with hepatitis B and hepatitis B virus-associated hepatocellular carcinoma

Abstract: Hepatitis B virus (HBV) infection is known as a serious problem in the domain of public health and approximately 350 million people across the world are affected with this infectious disease. As well, microRNAs are recognized as a type of small non-coding RNAs that can be widely used as a diagnostic biomarker and prognosis method of special diseases. In this respect, microRNA-122 or miR-122 can play a significant role in the pathogenesis of several hepatic diseases. Given the importance of microRNA-122 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 68 publications
1
8
0
1
Order By: Relevance
“…Li et al have reported that inhibiting SREBPs by Betulin can suppress HCC tumor-associated inflammation 55 . Inflammation in tumors, specifically induced by chronic viral infection, is critical for tumor-associated immune suppression and drug resistance 56–59 . Thus, we hypothesized that Betulin treatment on HCC tumor models can induce tumor regression and reduce drug resistance against chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al have reported that inhibiting SREBPs by Betulin can suppress HCC tumor-associated inflammation 55 . Inflammation in tumors, specifically induced by chronic viral infection, is critical for tumor-associated immune suppression and drug resistance 56–59 . Thus, we hypothesized that Betulin treatment on HCC tumor models can induce tumor regression and reduce drug resistance against chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-122 is a liver-specific miRNA that acts as a host factor to increase the abundance of HCV RNA by stabilizing the positive strand of HCV RNA genome and promotes HCV synthesis by binding two sites near the HCV 5' end and associating with Ago2 [34,[123][124][125]. In contrast to its role in HCV infection in HCC, miRNA-122 is significantly downregulated in patients with HBV infection [126,127]. Adenosine deaminases act on RNA-1 (ADAR1), an important gene involved in adenosine to inosine RNA editing and miRNA processing.…”
Section: Thyroid Hormone Induces An Anti-oxidative Stress Effect In Hepatocytes Mediated By Micrornasmentioning
confidence: 99%
“…The expression profile data of miR-122 in HCC patients (1330 HCC vs. 735 control) obtained from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus revealed the downregulation of miR-122 in HCC tissues [ 49 ]. Moreover, the serum and plasma levels of miR-122 were downregulated in HBV-infected HCC patients [ 50 , 51 ] (reviewed in [ 52 , 53 ]). It was also found that miR-122 was downregulated in the liver of chronic hepatitis B patients [ 54 , 55 ], HBV-infected cells, and HBV transgenic mice [ 56 ].…”
Section: Mir-122 In Hccmentioning
confidence: 99%